Accelerate IT and IoT with AIOps and observability - Valli Latha Narayanan; Sujatha N.; Mech Mukul; Lokesh V.S. (E3S Web of Conferences, 2024)
The most current of all disruptive technologies is artificial intelligence (AI), which has tremendous potential to transform marketing. AI is also the latest of all disruptive technologies. Professionals are scrambling to decide which artificial intelligence solutions will be the most advantageous for the specific projects they are working on. On the other hand, an exhaustive review of the relevant literature might highlight the significance of AI and serve as a roadmap for future study. This study on artificial intelligence (AI) aims to comprehensively analyze AI by doing a bibliometric, conceptual, and intellectual network analysis of the academic literature on the topic. Following a rigorous analysis of the publications, the most influential authors in the scientific community as well as the most trustworthy resources, were uncovered. The co-citation and co-occurrence analyses, respectively, helped along the building of the theoretical and philosophical network. Data clustering was beneficial in identifying study subthemes and future research subjects, which was done in order to improve the usage of artificial intelligence.